Characterization of Chlorella vulgaris (Trebouxiophyceae) associated microbial communities1. Issue 5 (22nd June 2020) - Haberkorn, Iris; Walser, Jean‐Claude; Helisch, Harald; Böcker, Lukas; Belz, Stefan; Schuppler, Markus; Fasoulas, Stefanos; Mathys, Alexander
Abstract : Microalgae exhibit extensive potential for counteracting imminent challenges in the nutraceutical, pharmaceutical, and biomaterial sectors, but lack economic viability. Biotechnological systems for contamination control could advance the economic viability of microalgal feedstock, but the selection of suitable strains that sustainably promote microalgal productivity remains challenging. In this study, total diversity in phototrophic Chlorella vulgaris cultures was assessed by amplicon sequencing comparing cultures subjected to five different cultivation conditions. Overall, 12 eukaryotic and 53 prokaryotic taxa were identified; Alphaproteobacteria (36.7%) dominated the prokaryotic and C. vulgaris (97.2%) the eukaryotic community. Despite altering cultivation conditions, 2 eukaryotic and 40 prokaryotic taxa remained stably associated with C. vulgaris ; diversity between systems did not significantly differ ( P  > 0.05). Among those, 20 cultivable taxa were isolated and identified by 16S rDNA sequencing. Subsequently, controlled co‐cultures were investigated showing stable associations of C. vulgaris with Sphingopyxis sp. and Pseudomonas sp.. Out‐competition of C. vulgaris due to ammonium or phosphate limitation was not observed, despite significantly elevated growth of Sphingopyxis sp. and Tistrella sp.. ( P  < 0.05). Nevertheless, C. vulgaris growth was impaired by Tistrella sp.. Hence, the study provides a selection of stable indigenous prokaryotes and eukaryotes for artificially tailoring microbial biocenoses. Following a bottom‐up approach, it provides a base for controlled co‐cultures and thus the establishment of even more complex biocenoses using interkingdom assemblages. Such assemblages can benefit from functional richness for improved nutrient utilization, as well as bacterial load control, which can enhance microalgal feedstock production through improved culture stability and productivity.